2018
DOI: 10.1002/aah.10005
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Onion or Ginger Modulates the Stress Response and Susceptibility to Vibrio harveyi JML1 Infection in Brown‐marbled Grouper Epinephelus fuscoguttatus Juveniles

Abstract: Onion Allium cepa and ginger Zingiber officinale have health-promoting properties that qualify them as functional foods. The effect of repeated acute stressors was examined in juvenile Brown-marbled Grouper Epinephelus fuscoguttatus that were fed four diets supplemented with onion at 1.8%, ginger at 1.8%, vitamin C at 0.86%, and β-glucan at 0.8% of the diet. The non-supplemented diet served as the control. After 12 weeks of feeding, fish were exposed to stressors and were experimentally infected with a fish pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Further, the fish were infected by intraperitoneal injection in the study by Amar et al. (), whereas they were cultured in sea water containing V. campbellii in our study. Finally, strain JML1 might be more virulent than strain BB120.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Further, the fish were infected by intraperitoneal injection in the study by Amar et al. (), whereas they were cultured in sea water containing V. campbellii in our study. Finally, strain JML1 might be more virulent than strain BB120.…”
Section: Resultsmentioning
confidence: 89%
“…These results are consistent with previous reports documenting the pathogenicity of Vibrio strains to various fish species, including kelp grouper ( E. bruneus ) (Harikrishnan, Balasundaram, & Heo, ), orange‐spotted grouper ( E. coioides ) (Nguyen et al., ) and hybrid grouper (E. fuscoguttatus x E. lanceolatus) (Shen et al., ). Very recently, pathogenicity of V. harveyi (strain JML1) was also documented in tiger grouper ( E. fuscoguttatus ) (Amar et al., ). The latter study reported higher mortality rates (80% or more after 4 days) than obtained in our study, which might be due to a number of factors.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Ginger ( Zingiber officinale ) and liquorice ( Glycyrrhiza glabra ) are two herbal extracts with promising properties as functional feed for aquaculture (Shakya, ; Smith, Christian, Taylor, Santander, & Rise, ; Tiwari et al, ). For example, ginger has been shown to improve immunity and enhance growth in several fish species such as tilapia ( Oreochromis mossambicus , Immanuel et al, ), European sturgeon ( Huso huso , Kanani, Nobahar, Kakoolaki, & Jafarian, ), carps ( Labeo rohita , Sukumaran, Park, & Giri, ), Rainbow trout ( Oncorhynchus mykiss , Nya & Austin, ; Shaluei, Nematollahi, Naderi‐Farsani, Rahimi, & Katadj, ), Asian sea bass ( Lates calcarifer , Talpur, Ikhwanuddin, & Ambok Bolong, ) and grouper ( Epinephelus fuscoguttatus , Amar, Apines‐Amar, & Faisan, ). Dietary supplementation of ginger extract maintained the morphology and function of the tissues and ameliorated the tissue damage following infection in Nile tilapia (Brum et al, ).…”
Section: Introductionmentioning
confidence: 99%